Extracellular vesicles derived from Trichinella Spiralis larvae promote the polarization of macrophages to M2b type and inhibit the activation of fibroblasts - Wu, Ji; Liao, Yao; Li, Dinghao; Zhu, Zifeng; Zhang, Lichao; Wu, Zhongdao; He, Ping; Wang, Lifu (Frontiers in Immunology, 2022)
Trichinella spiralis (T. spiralis) is a globally distributed food-borne parasite that can coexist with the host for a long time after infection. Trichinella-derived secretions can regulate the immune response and fibroblasts of the host, but the specific mechanisms involved are still unclear. The purpose of this study was to investigate the role of T. spiralis larvae-derived extracellular vesicles (EVs) and their key miRNAs in the process of T. spiralis–host interaction. In this study, we found that the EVs of T. spiralis larvae, as well as miR-1-3p and let-7-5p, expressed in T. spiralis larvae-derived EVs, can promote the polarization of bone marrow macrophages to M2b type while inhibiting the activation of fibroblasts. These findings will contribute to further understanding of the molecular mechanisms underlying T. spiralis–host interactions.